2012
DOI: 10.1155/2012/747924
|View full text |Cite
|
Sign up to set email alerts
|

Expenditure Pattern for TB Treatment among Patients Registered in an Urban Government DOTS Program in Chennai City, South India

Abstract: Background. Tuberculosis (TB) patients registered in the government clinics under the DOTS (Directly Observed Treatment, Short Course) program in Chennai city catering to about 4.3 million population. Objective. To estimate the pattern and overall costs incurred by the new patients (who have never had treatment for tuberculosis or have taken antituberculosis drugs for less than one month) registered under DOTS program in the treatment of tuberculosis in Chennai city. Methodology. A cross-sectional survey among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
21
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 6 publications
3
21
1
Order By: Relevance
“…[14]. Another study from Chennai, India reported a mean total cost of US$48 [9]. Mean total costs for TB care in South Africa and Nigeria were US$207 and $157 respectively [15,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[14]. Another study from Chennai, India reported a mean total cost of US$48 [9]. Mean total costs for TB care in South Africa and Nigeria were US$207 and $157 respectively [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Assuming the mean (SD) of total cost incurred by patients towards TB diagnosis and treatment as INR 3000 (100) [9], a minimum of 104 individuals were required for the study. All eligible participants were approached serially for the study and included until the desired sample size was reached.…”
Section: Methodsmentioning
confidence: 99%
“…For example, working days lost due to TB can range from 30 to 90 in South India (Muniyandi et al ., ; Muniyandi et al ., ). Subsequent indirect costs from loss of earnings can be substantial (Ananthakrishnan et al ., ), which would—in the absence of other forms of social insurance—importantly increase the insurance benefits provided by UPF. Third, there is a lack of a detailed description and corresponding pricing of the existing underlying mix of public versus private providers of TB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Tuberculosis (TB) disease is one of major global public health problems [1,2], with almost 1.6 million deaths in 2017 [3]. TB leads usually to enormous socioeconomic disturbance and hinders nation's development [4]. In this context, positive correlation was noticed between declining TB incidence rate and human development index [5].…”
Section: Introductionmentioning
confidence: 99%